Community Empowerment Program in Management of Health Clinic Development and Herbal Tourism - Adhi Iman Sulaiman; Toto Sugito; Bambang Suswanto; Tri Nugroho Adi; Sri Weningsih (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2021)
The herbal as a traditional medicine, that has become local wisdom of the Indonesian people needs to be preserved and developed in maintaining the health of families and communities. The study aims to creat community empowerment programs and support the development of health clinics and herbal tourism. The study used case studies method, and data were collected through observation, interviews, discussion and documentation. The study location took place in health clinic and herbal tourism, Kalibakung Village, Balapulang District, Tegal Regency, Central Java Province. The results showed that the raw materials of herbal plants to make herbal medicine in health clinics was still depend on the Center for the Development of Medicinal Plants and Traditional Medicines in Tawangmangu Regency. Plant galleries in herbal tourism are still pilot project only, it have not been developed to become self-sufficient of health clinics. Community groups need to be involved as partners to supplying raw materials of health clinics and herbal tourism develop with empowerment programs. Local governments must be initiate and facilitate the implementation of empowerment for collaboration with social institutions, universities and herbalists to conduct socialization, counseling, training and assistance on herbal plant cultivation and herbal processing. Empowerment programs have important to increase motivation, understanding, and community skills in cultivating and processing herbal plants to improving socio-economic welfare and supporting the development of health clinics and herbal tourism.